Quantitative assessment of sensory functions after 3 surgical approaches for trigeminal neuralgia by current perception threshold measurement - Ruoping, Chen; Huoniu, Ouyang; Bingyu, Wang; Meixiu, Ding; Hodge, Charles J. (Journal of Medical Colleges of PLA, 2008)
Objective： To quantitatively identify and grade trigeminal sensory functions after 3 major surgical procedures of trigeminal neuralgia using a newly developed quantitative sensory testing technique, current perception threshold measurement （CPTM）. Methods： In the current study, there were 48 trigeminal neuralgia patients without history of prior surgical treatment. These patients received one of the following 3 surgical procedures, microvascular decompression （MVD）, peripheral nerve block with alcohol （PNB）, or percutaneous radiofrequency thermocoagulation （PRFT）. The quantitative sensory testing measurement, CPTM, and conventional qualitative sensory testing measurements were performed preoperatively and postoperatively to evaluate and grade the trigeminal sensory functions All 3 major cutaneous sensory fiber types, large myelinated fibers （A beta）, small myelinated fibers （A delta） and unmyelinated fibers（C） were allowed to quantitatively evaluate and grade by CPTM. The results of the measurements were statistically analyzed using a one-way analysis of variance （single factor）. Each subject was his/her own control for comparison of the preoperative to postoperative state on the asymptomatic and symptomatic sides. Subjects were tested 48 h preoperatively and 4 weeks postoperatively. Results： PNB with alcohol and PRFT caused significant sensory dysfunction postoperatively in every fiber type, indicating damage to all fibers. On the contrary, the sensory function in all 3 fiber types was unchanged after MVD management. Conclusion： Among the 3 major surgical procedures tested, only MVD preserves sensory function in trigeminal system. CPTM is of quantitative nature on the evaluation of sensory functions of nerve fibers